2016
DOI: 10.15761/cmid.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Real-time PCR versus ELISA in the diagnosis of cytomegalovirus infection in pregnant women

Abstract: Background: Cytomegalovirus infections are endemic worldwide. The most frequently used methods for detecting antibodies in developing world are the enzyme linked immunosorbent assay. The polymerase chain reaction is a molecular biology technique in which the production of large amounts of specific deoxyribonucleic acid fragments is induced from very low concentrations of complex substrates allowing the detection of very low amounts of viral particles.Objectives: To assess the accuracy of ELISA tests in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Out of 57 cases, 6 (10.53%) were positive for CMV IgM, 50 (87.72%) were positive for CMV IgG and 18 (31.58%) were positive for CMV DNA by PCR. In our study, out of 18 cases positive for CMV DNA, 6(33.34%) cases were having viral load 1x10 3 IU/ml, and 4(22.22%) cases each of having viral load 1x10 4 IU/ml, 1x10 5 IU/m and 1x10 6 IU/ ml respectively (Table 1). In our study, out of 50 CMV IgG seropositives, 15 cases were positive for CMV DNA by PCR and 35 cases were negative for CMV DNA ( Table 2).…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…Out of 57 cases, 6 (10.53%) were positive for CMV IgM, 50 (87.72%) were positive for CMV IgG and 18 (31.58%) were positive for CMV DNA by PCR. In our study, out of 18 cases positive for CMV DNA, 6(33.34%) cases were having viral load 1x10 3 IU/ml, and 4(22.22%) cases each of having viral load 1x10 4 IU/ml, 1x10 5 IU/m and 1x10 6 IU/ ml respectively (Table 1). In our study, out of 50 CMV IgG seropositives, 15 cases were positive for CMV DNA by PCR and 35 cases were negative for CMV DNA ( Table 2).…”
Section: Resultsmentioning
confidence: 51%
“…15 A study conducted by EI Sanousi et al reported prevalence of CMV DNA 29.7% among pregnant women. 6 However, Aliyu et al reported detection of 45% CMV DNA among HIV seropositives. 16 Shukla et al reported prevalence of CMV DNA of 49% in India.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations